Practicalities of language data collection and management in and around Indonesia - Klamer, Marian; Edwards, Owen; Fricke, Hanna; Gialitaki, Zoi; Palmér, Axel; Saad, George; Sulistyono, Yunus; Visser, Eline; Wu, Jiang; Moro, Francesca (UI Scholars Hub, 2021)
Researchers use different approaches when collecting and managing primary language materials during fieldwork. Yet it is important that this work is done in a transparent way, so that it can be used by other researchers, who might have other aims, as well as by the speaker community who might want to use or take note of the collected materials. In this article we use our research experience in language data collection in and around Indonesia in fieldwork projects of three kinds: descriptive fieldwork, linguistic surveys, and projects investigating language contact. Our aim is to provide an introductory and practical guide for students and professionals who are embarking on fieldwork in or around Indonesia. Describing practical methods of language data collection, processing, and management, our aim is to provide a guide for any research which involves the collection of language materials, including linguistic research, oral history or literature, and ethnography.